Guardian of Image: Evaluating Corporate Reputation as a Shield Against COVID-19 Fallout on Firm Performance - Salsabila Nabilah Aliyah (Journal of Economics, Business, and Accountancy Ventura, 2024)
The COVID-19 pandemic has wreaked havoc on the global economy and posed a significant challenge for companies to survive. This research provides empirical evidence on how the pandemic can adversely affect company performance. Furthermore, the study also unravels how a company's reputation can act as a shield amid the onslaught of the pandemic, thereby moderating the negative relationship between COVID-19 and company performance. The research utilizes 2,847 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2022. The analysis employed in this study uses moderated regression analysis (MRA) with STATA software. The results indicate that a company's reputation can moderate, weakening the negative relationship between COVID-19 and company performance. These findings are reinforced by robustness testing using Coarsened Exact Matching (CEM) and alternative performance measurements. This information is highly valuable for companies and stakeholders, indicating that the risks arising from the COVID-19 pandemic can be mitigated by strengthening the company's reputation.